ANALISIS RETURN ON EQUITY (ROE), DEBT TO ASSETS RATIO (DAR), DAN PRICE BOOK VALUE (PBV) TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2012 - B11110142, Meista Carolin (Jurnal Manajemen Update, 2014)
The Increasing growth in Real Estate and Property sector and its stable stock price even increasing stock price in economic depression period makes Real Estate and Property sector attractive to be analyzed. The purpose of this study is to determine the level of influence Return On Equity (ROE), Debt to Assets Ratio (DAR), and Price Book Value (PBV) on stock return company Real Estate and Property sector listed in Indonesia Stock Exchange 2009-2012. The population in this study are all Real Estate and Property companies sector listed in Indonesia Stock Exchange 45 companies in 2009-2012. The samples were chosen using purposive sampling method. The number of samples in this study were as many as 32 companies. Data collection was done by taking documents from the Indonesian financial statements Capital Market Directory and download the official website of the Indonesian Stock Exchange in www.idx.co.id. The analysis used in this study are multiple linier regression. The result of this study indicate that the variables ROE, DAR, and PBV simultaneously have a significant impact on stock return. Further research also showed that partial variable ROE and DAR has no significant effect on stock return, while PBV variable have a significant effect on stock return. The conclusion of this research is that multiple regressions model formed by ROE and DAR can’t be used to predict stock return, while PBV can be used as predictor to predict stock return. Keywords:       Stock return, Return On Equity (ROE), Debt to Assets Ratio (DAR), and Price Book Value (PBV)